The double burden of COVID-19 and cancer at the Uganda Cancer Institute - Natalie Anumolu; Matida Bojang; Pius Mulamira; Courtney Jankowski; Kia Lechleitner; Sarah Abunike; Simon Kasasa; Robert Lukande; Nixon Niyonzima; Kirsten Beyer (Journal of Global Health Reports, 2024)
# Background